Intriguing photophysical and mechanochromic characteristics of carboline-based benzothiadiazole donor‒acceptor triad compounds. (September 2022) - You, Dong Kyun; Kim, Mingi; Yi, Sanghee; Seo, Yung Ju; Lee, Wonchul; Lee, Kang Mun
Abstract: Three novel carboline-based benzothiadiazole compounds, αCB, βCB, and γCB, bearing α-, β-, and γ-carboline, respectively, were synthesized and characterized. The molecular structures of αCB and γCB in the crystalline state were analyzed using single-crystal X-ray diffraction. The UV–vis absorption and photoluminescence spectra of all compounds displayed typical intramolecular charge transfer (ICT) characteristics, resulting in clear solvatochromic effects in various organic solvents. Theoretical calculations also verified that the major electronic transitions of the three compounds could be assigned to the ICT transition between the carboline moiety (as the electronic donor, D) and benzothiadiazole center (as the acceptor, A). The unit cell of the crystal structure of αCB revealed two solvent (chloroform) molecules residing in the space between the two α-carboline moieties via hydrogen bonding, which could inhibit the structural fluctuation of this compound. Given this feature, αCB demonstrated higher emissive efficiency and a lower nonradiative decay process compared with βCB and γCB . Interestingly, the crystalline powders of αCB, including the solvent molecules in its unit cell, demonstrated a high-contrast and reversible mechanochromic phenomenon, which originated from the conversion of the compound from a crystalline state to a randomly aggregated one. The above findings provide insights into the molecular design of carboline-based D‒A‒ D-type organic fluorophores with high emissive efficiency and intriguing functional characteristics. Graphical abstract: Image 1 Highlights: The first examples of donor‒acceptor‒donor (D‒A‒D) type α-, β-, and γ-carboline-based benzothiadiazole compounds. Intramolecular-charge-transfer characteristic via distinct solvatochromic effect and high quantum efficiency. High-contrast and reversible mechanochromism phenomenon in the process of grinding sample and fuming CHCl3 vapor. Insight for molecular design of carboline based D‒A‒D type organic fluorophores.